Geologia e tectônica do intervalo Serra do Engenho Novo - Sumaré, no Estado da Guanabara - Gaglianone, Paulo César (1971)
During the course of the present work, are reported some comparative field data, with statistic analysis from serra do Engenho Novo, Sumaré and Borem in Guanabara State. The metasedimentary rocks of the region belonging to the precambrian are widely distributed. They comprise a considerable porttion of the "Fundamental Complex" as gneisses and migmatites and a younger granitic intrusion om the ocidental margin of serra do Engenho Novo. They have been affected by different degrees of fpldings and the diagrams (s-pole and frequence of linear structures) show the effect of interference by superposed foldings. The overall relationship suggest that the structure of serra do Engenho Novo is different from the other areas and they are very complex.